Errors associated with compound‐specific δ15N analysis of amino acids in preserved fish samples purified by high‐pressure liquid chromatography. (4th May 2020) - Swalethorp, Rasmus; Aluwihare, Lihini; Thompson, Andrew R.; Ohman, Mark D.; Landry, Michael R.
Abstract: Compound‐specific isotopic analysis of amino acids (CSIA‐AA) is increasingly used in ecological and biogeochemical studies tracking the origin and fate of nitrogen (N). Its advantages include the potential for resolving finer‐scale trophic dynamics than possible with standard bulk SIA and for reconstructing historical changes in the food webs of consumers from analyses of specimens in preserved sample archives. For the latter, assessing the effects of chemical preservatives on δ 15 NAA has been inconclusive because the conventional CSIA approach for derivatized AAs by gas chromatography‐combustion‐isotope ratio mass spectrometry (GC‐C‐IRMS) has analytical errors (0.4–1.0‰) in the range expected from chemical preservation. Here, we show improved analytical precision (0.15 ± 0.08‰) for 11 underivatized AA standards analyzed by high‐pressure liquid chromatography followed by offline elemental analysis‐IRMS (HPLC/EA‐IRMS). Using this method, we report the first high‐precision tests of preservation effects on δ 15 NAA in Northern Anchovy ( Engraulis mordax ) kept 1.5‐yr in ethanol and up to 27‐yr in formaldehyde. We found minimal methodological induced fractionation for eight AAs, and preservation effects on δ 15 N were similar regardless of duration and preservative used. Although some of the AAs differed significantly from frozen control samples (AA average +1.0 ± 0.8‰), changes in δ 15 N in the source AA phenylalanine and trophic position estimates were statistically insignificant. Our results are encouraging for resolving fine‐scale natural variability using HPLC/EA‐IRMS on chemically preserved specimens and for ultimately reconstructing biogeochemical records and trophic dynamics over long time scales.